2011
DOI: 10.12693/aphyspola.119.186
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Magnetoresistance and Its Anisotropy of Thin Polycrystalline La0.83Sr0.17MnO3Films in High Pulsed Magnetic Fields

Abstract: The results on the study of grain boundary effects and influence of film deposition conditions on the magnetoresistance and its anisotropy in polycrystalline La0.83Sr0.17MnO3 films are presented. The magnetoresistance was measured in high pulsed magnetic fields up to 25 T (pulse duration ≈ 0.6 ms) in the temperature range of 120-300 K. A modified Mott hopping model was applied to describe the main behavior of high-field magnetoresistance for both ferromagnetic and paramagnetic phases of the polycrystalline fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…4). It is known that in thin manganite films the direction of the easy axis of magnetization is parallel to the film plane due to the fact that the demagnetization field is directly linked with the geometric shape of the sample [1516]. In our case, this effect is partly compensated by the columnar structure of the film, where each individual crystallite has the easy axis of magnetization directed perpendicular to the film plane.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…4). It is known that in thin manganite films the direction of the easy axis of magnetization is parallel to the film plane due to the fact that the demagnetization field is directly linked with the geometric shape of the sample [1516]. In our case, this effect is partly compensated by the columnar structure of the film, where each individual crystallite has the easy axis of magnetization directed perpendicular to the film plane.…”
Section: Resultsmentioning
confidence: 76%
“…The manganite films consisting of columnar nanograins have already been successfully applied for the sensing of high pulsed magnetic fields (B-scalar sensor) [1314]. Despite this development, the scalar (independent of field orientation) CMR effect under a low magnetic field is still a challenging goal towards practical applications due to low sensitivity and large magnetic anisotropy [1516]. For this reason, the investigation and control of the magnetoresistive properties of manganite materials on the nanometer scale is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…3a). It is known that the demagnetisation field is high due to the high aspect ratio of the sample [18]. However, the long-range ferromagnetic order at low temperatures is found only in single crystals or epitaxial films.…”
Section: The Ageing Influence On the Magnetoresistance Of Lsmo Filmsmentioning
confidence: 99%
“…Moreover, for the application of the CMR-B-scalar sensors for measurements of smaller magnetic fields (b 0.5 T), the role of magnetoresistance anisotropy (MRA) significantly increases [2]. It was demonstrated that the main reason of the MRA in thin polycrystalline films is demagnetization effect [10]. This phenomenon increases inaccuracy of measurement of magnetic field magnitude at low fields.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon increases inaccuracy of measurement of magnetic field magnitude at low fields. In thin polycrystalline films the demagnetization effect depends not only on the aspect ratio of the film, but also on the magnetic interaction between grains in film plane [8,10]. Magnetic decoupling is thought to be the result of interfacial effects of grains and depends on grain boundary (GB) material which might be assumed as ferromagnetic regions with suppressed magnetic order [11] due to a high number of various defects, created during film deposition process.…”
Section: Introductionmentioning
confidence: 99%